ANALYSIS OF ADAPTIVE NEGATIVE STIFFNESS DEVICE FOR SEISMIC PROTECTION OF R.C.C PLANE FRAME STRUCTURE - N. T. Ghadge; Dr. H. S. Jadhav (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Seismic forces and displacements in existing structures can be effectively reduced in an approach where the structure in intentionally weakened and damping is added. Intentionally weakened means the strength and stiffness are reduced. However, the approach also results in permanent deformations and inelastic movements of the structural system during a seismic event. In this paper, a new concept which imitates weakening by incorporating a mechanical system that produces true negative stiffness in the structural system is taken. A plane frame and space frame are modeled in SAP 2000 software by incorporating negative stiffness device and viscous dampers for comparing it with frames without negative stiffness device and dampers. Validation is done by modeling the experimental model done by authors in SAP 2000 and the result comparison is done for it.